PENGARUH BOPO, NPL DAN LDR TERHADAP RETURN ON ASSET DENGAN NET INTEREST MARGIN SEBAGAI VARIABEL INTERVENING (Studi pada Bank Umum Go Public yang Terdaftar di BEI Periode 2015- 2019) - Farhanditya, Ferdiansyah Djody; Mawardi, Wisnu (Faculty of Economics and Business Diponegoro University, 2021)
BSTRACT In this research study, the objective of this research is to examine the effect of Operational Cost of Operating Income (BOPO), Non Performing Loan (NPL), Loan to Deposit Ratio (LDR) to Return on Assets and Net Interest Margin (NIM) as intervening variables. The population used in this study are conventional commercial banks in Indonesia that have been listed on the Indonesia Stock Exchange (IDX) for the period 2015-2019. The data used in this study are secondary data with a total sample of 26 banks, where the sampling uses purposive sampling method.. The analysis technique used in this study is multiple linear regression and path analysis. The results of this study found that BOPO had a significant negative effect on NIM, NPL had a positive but insignificant effect on NIM, while LDR had a negative but not significant effect on NIM. BOPO has a negative and significant effect on ROA. NPL has a negative but not significant effect on ROA. LDR has a positive but not significant effect on ROA. NIM has a positive and significant effect on ROA. Furthermore, NIM is not proven in mediating BOPO and NPL against ROA. However, NIM is proven to mediate LDR against ROA